Molecular Survey on Symbiodinium of Some Scleractinean Coral Spp. and a Fire Coral sp. along the Red Sea of Egypt - Y. Dosoky Muhammad; F. Madkour Fedekar; I. Ahmed Mohamed; H. Hanafy Mahmoud (International Marine Science Journal, 2019)
The present study introduce an overview on the cladal structure of Symbiodinium population associated with some species of scleractinean corals and fire coral in the Egyptian Red Sea coast and discuss the possible consequences of recent climate changes on coral reefs. Cladal structure of Symbiodinium populations associated with eight keystone species of scleractinean corals and one species of fire coral that collected along Egyptian Red Sea coast, during 2012-2013, had been resolved based on 18S nrDNA and ITS2 genetic markers. Only Symbiodinium subclades C1 and A1 were identified from all examined species. Symbiodinium C1 was the dominant subclade that associated with 61% of coral samples. Results revealed that the studied pocilloporid corals were associated with Symbiodinium C1 and/or A1 while acroporids were only associated with Symbiodinium C1. The present data also indicated that Symbiodinium C1 occurred at high densities than A1 or A1+C1 combination. Because of the relative thermal susceptibility of clades C and A, the current study addresses that the recent climate changes may derive dramatic changes on community structure of coral reefs at the Red Sea.
Keywords: Genetic diversity